Cover Journal of Infrastructure & Facility Asset Management - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2019)
Prediction of Rust Thickness in Reinforced Concrete Structures to Enhance the Asset Management for Coastal Infrastructures    Wahyuniarsih Sutrisno, I Ketut Hartana & Priyo SuproboSimulation of Concerete Slab Bevahior to Explosion    M. Shabib Al Bari, Januarti Jaya Ekaputri, Faimun, Julendra Bambang Ariatedja,    Buntara S. GanLearning IFAM by using ITS Medical Centre as a Case: #1 - Identifying the Function, Medical Service, Infrastructure & Facility   Vita Ratnasari & Hitapriya SuprayitnoPotential Number of Passenger and Performance Evaluation of Surabaya School Bus    Adhi Muhtadi, Sapto Budi Wasono, Hitapriya Suprayitno & Ervina AhyudanariAssessment of Infrastructures Assets Induced by Water Level  Fluctuation along the Bengawan Solo River    T. R. Satrya, R. A.A Soemitro, M. A Maulana, D.D. Wamana & R. SoetantoRoad Network Connectivity Quality Assesment for Timor Leste National Road Network    Frans de Jesus Babo & Hitapriya Suprayitno